Recovery of Motor Function Following Spinal Cord Injury 2016
DOI: 10.5772/62947
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Spinal Cord Injury Models in Rodents: Anatomical Correlations and Assessment of Motor Recovery

Abstract: Human traumatic spinal cord injury (SCI) causes disruption of descending motor and ascending sensory tracts, which leads to severe disturbances in motor functions. To date, no standard therapy for the regeneration of severed spinal cord axons in humans exists. Experimental SCI in rodents is essential for the development of new treatment strategies and for understanding the underlying mechanisms leading to motor recovery. Here, we provide an overview of the main rodent models and techniques available for the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 124 publications
0
4
0
Order By: Relevance
“…Dependent on the pathology of injury, the spinal cord can recover spontaneously (e.g., by axons bypassing the lesions, so-called sprouting) except total transection, which is known to be not able to regenerate spontaneously in humans and rats [ 5 ]. Even though spinal cord regeneration after complete transection has been described in various animal studies with diverse therapeutic strategies [ 6 ], there is still no convincing standard curative therapy available for humans.…”
Section: Introductionmentioning
confidence: 99%
“…Dependent on the pathology of injury, the spinal cord can recover spontaneously (e.g., by axons bypassing the lesions, so-called sprouting) except total transection, which is known to be not able to regenerate spontaneously in humans and rats [ 5 ]. Even though spinal cord regeneration after complete transection has been described in various animal studies with diverse therapeutic strategies [ 6 ], there is still no convincing standard curative therapy available for humans.…”
Section: Introductionmentioning
confidence: 99%
“…In their review of the many works on spinal cord injury, Vogelaar and Estrada [1] showed that the most popular methods for gait evaluation are the Basso, Beattie, and Bresnahan (BBB) locomotor score and subscore (for rat) and the Basso Mouse Scale (BMS, for mouse) determination, horizontal ladder rung test and gridwalk, automated gait analysis methods, MotoRater and kinematic analysis, sensory tests, and forelimb tests. Of these methods, the automated gait analysis methods have been increasingly utilized in recent years, based on the volume of scientific works describing their use.…”
Section: Introductionmentioning
confidence: 99%
“…Especially these intrinsic regeneration mechanisms are interesting targets for regeneration-promoting treatments, since many treatments exist that reduce the inhibitory barrier, but the lack of intrinsic axon outgrowth is still a great limiting factor (Bradke et al 2012;Bunge 2008). Testing of putative treatments is mostly performed in animal SCI models, is time-consuming and expensive and involves the use of large numbers of animals (Abu-Rub et al 2010;Robins and Fehlings 2008;Vogelaar and Estrada 2016). An in vitro model for CST regeneration would greatly accelerate the screening for treatments that increase the intrinsic regenerative capacity of CST axons.…”
Section: Introductionmentioning
confidence: 99%